Tingkat Pengetahuan Ibu Pemberian Makan Bayi Dan Anak (PMBA) Dengan Status Gizi Baduta Usia 12-24 Bulan Di Desa Ajibarang Wetan Tahun 2024 - purwaningsih, rahmawati tri; Isnaeni Rofiqoch (NERSMID : Jurnal Keperawatan dan Kebidanan, 2024)
The aim is to analyze the relationship between the level of maternal knowledge about infant and young child feeding (PMBA) and the nutritional status of toddlers aged 12-24 months in Ajibarang Wetan Village in 2024. The research method is quantitative analytical correlation with a Cross Sectional study design. The study population was 68 and the number of samples was 51 mothers who had toddlers aged 12-24 months in Ajibarang Wetan Village. The sampling technique was purposive sampling. The level of knowledge was measured by a questionnaire and the nutritional status of toddlers was seen based on weighing and the KIA book. Data analysis used the Spearman's rho statistical test through the SPSS application. The results of this study indicate that most respondents with poor nutritional status of toddlers have sufficient knowledge (21.6%), most respondents with good nutritional status of toddlers have good knowledge (70.6%), and most respondents with nutritional status of toddlers at risk have good knowledge (2.0%). The results of the Spearman's rho test obtained a p-value of 0.000 <0.05, which means that there is a relationship between the level of knowledge and the nutritional status of toddlers. Conclusion: There is a significant relationship between the Level of Knowledge About Infant and Child Feeding (PMBA) and the Nutritional Status of Toddlers Aged 12-24 Months in Ajibarang Wetan Village in 2024.